Typological characterization of the Portuguese traditional schist constructions - Barros, R. S. (2012)
Schist constructions represent an important cultural, architectural and historical legacy in Europe, and particularly in Portugal, that urges to preserve. Included among the traditional Portuguese architectural heritage, there are many traditional buildings in schist masonry, distributed from North to South, varying the types of buildings, the constructive methodologies and even the material schist, which may vary in properties and characteristics, depending on the region where it is extracted. Over the years, this traditional architecture has implemented a sustainable construction through the use of natural materials available in the region, as today it is desired to implement in the contemporary construction practice. The constructive techniques and solutions of these traditional structures have been developed in direct relation with various factors as economic, environmental and social, adapting to different requirements over the time, originating a wide diversity of construction typologies that today exist in Portugal. The present study intends to describe and characterize the different building typologies of the traditional schist construction in Portugal mainland. Examples of more prominent constructions, considering its dimensions and/or patrimonial importance are presented and analyzed.